2018
DOI: 10.1097/md.0000000000013635
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of apatinib in patients with advanced colorectal cancer as the late-line treatment

Abstract: There is currently no standard therapeutic regimen available for patients with advanced colorectal cancer in whom the disease continues to progress after 2 or more lines of chemotherapy. The purpose of this study is to investigate the efficacy and safety of apatinib in patients with advanced colorectal cancer for whom at least two lines of prior chemotherapy had failed.Twenty seven patients with advanced colorectal cancer who had failed at least 2 lines chemotherapy were treated with apatinib (500 mg/day). As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
(31 reference statements)
2
20
1
Order By: Relevance
“…The moderate initial dose in our study resulted in a more manageable toxicity profile and a lower proportion of dose modification than those in the previous studies of apatinib 850 mg in advanced gastric cancer 33,34 . Furthermore, it seems comparable to the modification reported in the studies of apatinib 500 mg in mCRC 10,[13][14][15][16] .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The moderate initial dose in our study resulted in a more manageable toxicity profile and a lower proportion of dose modification than those in the previous studies of apatinib 850 mg in advanced gastric cancer 33,34 . Furthermore, it seems comparable to the modification reported in the studies of apatinib 500 mg in mCRC 10,[13][14][15][16] .…”
Section: Discussionsupporting
confidence: 85%
“…This finding further supports the use of apatinib as an alternative option based on the strategy of continued administration of newer anti-angiogenic agents as the new standard of care. In a retrospective case-controlled study, apatinib exhibited weaker survival outcomes with PFS and OS of 2.0 and OS 5.0 months, respectively, in late-line setting in mCRC 16 . We speculated that the inconsistency could be because the previous study had a relatively shorter follow-up time (6.0 months), higher proportion of patients with performants status of 2 (48.1%), smaller sample size (25 patients in apatinib group), and higher selection bias than those of our present study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Management of the patients in retrospective study was not sufficient and normative compared with a well-designed phase ІІ clinical trial, which was demonstrated in the other retrospective study of apatinib in metastatic CRC (ORR=3.7%, DCR=70.4% and mPFS=2.0 months). 36 Additionally, it should be noted that the proportion of patients with ECOG 2 score in our study was higher than that in the phase ІІ study (43.5% vs 35.4%). To our knowledge, the previous research had suggested that higher ECOG score was associated with worse prognosis among patients with metastatic CRC.…”
Section: Discussioncontrasting
confidence: 64%
“…It has been approved as a second-line therapy in Chinese patients with advanced HCC. The systemic adverse events including gastrointestinal reaction, hypertension, abnormal coagulation function, proteinuria after oral administration were still common and even serious (Zhao et al., 2018 ), although improved survival occurred in advanced HCC, non-small-cell lung cancer and colorectal cancer (Liao et al., 2018 ; Wang et al., 2018 ; Wu et al., 2018 ). The local delivery of drug is a novel method to increase tumor drug concentration and reduce systemic toxicity (Zhou et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%